La alimentación infantil para el desarrollo evolutivo de los niños de preparatoria de la escuela de educación básica Julio María Matovelle de la ciudad de Loja. Periodo lectivo 2017-2018 - Quinche Granda, Ulises Omar (2018)
This research work called: CHILDREN'S FOOD FOR THE EVOLUTIONARY DEVELOPMENT OF CHILDREN OF PREPARATORY OF THE BASIC EDUCATION SCHOOL JULIO MARÍA MATOVELLE OF THE CITY OF LOJA. LEGAL PERIOD 2017-2018. It was proposed as General Objective: Identify the main food problems that affect the evolutionary development of high school children of the basic education school Julio María Matovelle, within the research used the scientific method, analytical-synthetic and descriptive. The techniques and instruments used to prepare this research work were: The body mass index, the interview applied to the teacher, questionnaire to parents, the observation guide aimed at children. The sample consisted of a teacher of first year of Basic Education parallel "B" and 20 students. The results obtained during the interview were: The teacher indicates that infant feeding influences the evolutionary development of children. Regarding the questionnaire: the parents are unaware of the issue of feeding and how this can affect their development also applied the body mass index that instrument contributed to the result of the initial diagnosis and facilitated the entire research process, through these results, the alternative programmed proposal was used. From the results obtained, it is concluded that nutrition directly influences children's developmental development, which is why care must be taken and more attention given to this issue since it is of great importance to society, as well as being a problem. that is ending the lives of human beings either at an early age or during adulthood and it is recommended that educational authorities and parents pay more attention to the problem of poor nutrition since it is a negative factor today. It affects society in general.